ANALISIS APLIKASI SISTEM DIGITAL MARKETING BERBASIS WEBSITE PADA USAHA OBAT HERBAL MENGGUNAKAN SAKA 1.0 (STUDI KASUS: PT. DIGI HERBA NUSANTARA) - Mahaska Aiden Wibisono Mahaska Aiden Wibisono; Achmad Lutfi Fuadi (Kampus Akademik Publiser, 2026)
Abstract. This study aims to analyze and develop a web-based digital marketing system application named Saka 1.0 at PT. Digi Herba Nusantara. The application is designed to fulfill the operational needs of employees, including Advertiser, Customer Service, and Supervisor, in managing advertising expenditure data, sales revenue data, operational reporting, and real-time performance monitoring. The research was carried out through system requirements analysis, design, and implementation of a web application using the Laravel Framework as the primary development foundation. The system is also integrated with the external platform Meta Business Suite to support digital advertising management processes. The results indicate that the Saka 1.0 application successfully improves the efficiency of data recording and management processes, accelerates report generation, and provides more accurate and real-time performance monitoring features for supervisors. This research contributes to the development of web-based information systems in the field of digital marketing, particularly in the integration between internal company systems and external digital marketing platforms. Keywords: information system, website-based application, digital marketing, Laravel Framework, system analysis, real-time monitoring, Saka 1.0, system integration.